2020
DOI: 10.2144/btn-2020-0126
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoretic Characterization of Dendritic Cell Deformability Upon Maturation

Abstract: We have developed a rapid technique for characterizing the biomechanical properties of dendritic cells using dielectrophoretic forces. It is widely recognized that maturing of dendritic cells modulates their stiffness and migration capabilities, which results in T-cell activation triggering the adaptive immune response. Therefore it is important to develop techniques for mechanophenotyping of immature and mature dendritic cells. The technique reported here utilizes nonuniform electric fields to exert a substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In addition to this, an increase in the density of both the microtubules and the intermediate filaments in heart failure has been observed [ 27 ]. Other studies have shown that the CSK is involved in dendritic cells (DCs) maturation, which activates T cells, through the remodeling of the actin filaments [ 28 ]. This CSK alteration leads to an increase in the cell’s stiffness which, in turn, promotes T cells priming [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, an increase in the density of both the microtubules and the intermediate filaments in heart failure has been observed [ 27 ]. Other studies have shown that the CSK is involved in dendritic cells (DCs) maturation, which activates T cells, through the remodeling of the actin filaments [ 28 ]. This CSK alteration leads to an increase in the cell’s stiffness which, in turn, promotes T cells priming [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…We and others postulate that T cells conduct physical reconnaissance prior to invoking an immunological action, and this is based on two observations. The first is the immunological kinapse activity mentioned above, and the other is that DC increases their stiffness by 2-3-folds during their maturation process, [96][97][98][99] in addition to upregulating their T cell activation markers MHCII, CD80/ CD86, and cytokines. [90,100,101] Studies use well-defined substrates with functionalized surfaces to act as aAPCs with tunable stiffness; such systems allow the decoupling of stiffness from ligand presentation.…”
Section: Stiffness Of Aapc In T Cell Activationmentioning
confidence: 99%
“…In particular, single cell mechanics is of interest in modern cell biology and immunology. It allows prediction of pathogen infected cells [150], maturation stage of dendritic cells [151,152], and T cell and antigen-presenting cell interactions [153,154]. Cell mechanics has been hypothesized to alter as an adaptation mechanism to microgravity since it might be correlated to cytoskeleton remodeling [55,56,58].…”
Section: Technological Advances For Future Microgravity Researchmentioning
confidence: 99%